Teacher Turnover in Private Primary Schools in Azerbaijan: Contributing Factors - Eyvazova, Elshana; Jabrayilli, Fidan; Gasimova, Chinara; Veyisova, Gunel; Narimanli, Leyla (ADA University, 2025)
This capstone project explores the multifaceted factors of teacher turnover in private primary schools in Azerbaijan using qualitative data from semi-structured interviews with teachers and school administrators. The research identifies four primary factors of turnover: excessive workload, insufficient professional development opportunities, financial constraints, and a lack of effective leadership support. Some of these private schools have tried to implement retention strategies, such as informal recognition schemes, wellbeing activities, and some recognition of informal roles. These efforts are often inconsistent and lack strategic alignment. These findings underscore the importance of more comprehensive retention strategies, including active mentorship for novice teachers, tailored professional development plans to foster career advancement, and targeted professional development plans to foster career growth, and leadership training focused on supportive, transparent communication. Furthermore, financial rewards as well as initiatives promoting a balanced personal and professional life were regarded as critical to teacher retention and enhanced engagement. This research adds to the emerging literature on teacher turnover in the post-Soviet education frameworks and offers practical suggestions for school administrators aiming to create more favorable employment conditions for teachers in Azerbaijan’s private educational landscape.
Keywords: Teachers -- Recruiting.; Teachers -- Job satisfaction.; Teachers -- Professional development.; Teachers -- Supply and demand.; Educational leadership -- Management.; Work-life balance -- Education sector.